Agrochemical and Microbiological Characteristics of Soils in Termez and Muzrabod Districts - Abdullaeva G. K. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Soils in arid regions often experience declining fertility due to low organic matter, salinization, and intensive irrigation, which challenge sustainable agricultural productivity. Specific Background In the Surkhandarya Region of Uzbekistan, rice-growing areas of Termez and Muzrabod exhibit severely depleted humus levels, moderate salinity, and weak structural stability. Knowledge Gap Despite evidence that microalgae and cyanobacteria can improve soil fertility in arid environments, their potential for biorecultivation under the specific climatic and edaphic conditions of southern Surkhandarya remains insufficiently documented. Aims This study assessed key agrochemical properties and microbiological communities while evaluating the nitrogen-fixing activity and soil-ameliorating potential of native phototrophic microorganisms. Results Findings revealed low humus (1.0–1.5%), moderate salinity (EC 2.58–8.55 mS/cm), and active populations of Nostoc, Anabaena, Oscillatoria, Klebsormidium, and Chlorella with nitrogen fixation rates of 3.2–3.7 mg N g⁻¹ day⁻¹. Klebsormidium inoculation increased organic matter by 20–25%, improved aggregate stability, reduced bulk density, and enhanced water-holding capacity by 12–15%. Novelty This work provides integrated chemical–biological evidence demonstrating the efficacy of locally adapted microalgae for soil restoration in BWk desert climates. Implications The results support microalgae-based biorecultivation as a viable strategy for rehabilitating degraded arid soils and strengthening sustainable land management in Central Asia.Highlight : The content emphasizes that low humus levels and moderate salinization remain key factors reducing soil fertility in arid Surkhandarya regions. The role of cyanobacteria and microalgae is highlighted through their ability to fix nitrogen, strengthen soil aggregates, and enhance organic matter. Experimental findings show that microalgal inoculation, especially Klebsormidium, measurably improves soil structure and water retention, supporting its potential for sustainable biorecultivation. Keywords : Soil, Humus, Agrochemical Analysis, Cyanobacteria, Microalgae